Hubungan Sanitasi Lingkungan Rumah Tangga dengan Kejadian Stunting pada Balita Usia 0-60 Bulan - Tya Nadila; Linawati Novikasari; Setiawati Setiawati (Universitas Malahayati Lampung, 2023)
ABSTRACT Stunting is a disorder of the linear growth of a child's body to become short or very short based on height for age with a threshold (Z-score) -2 SD. Data on children attending posyandu at the Karang City Health Center by looking at the number of children aged 0 months to 5 years there were 162 children, with the distribution of the number based on the age of 5 years 36 children, 4 years 25 children, 3 years 35 children, 2 years 40 children, aged 1 year 16 children, aged 12 months 12 children. Know the correlation between household environmental sanitation and the incidence of stunting in toddlers aged 0-60 months in the Working Area of the Karang Bandar Lampung Health Center in 2022. This study used quantitative method. The design in this study used an analytical survey design with a cross sectional approach. The sample in this study were all toddlers aged 0-6 months. The sampling technique in this study was random sampling. Analysis on univariate and bivariate tests using the chi square test. Household environmental sanitation in the Working Area of the Karang Bandar Lampung City Health Center in 2023 was 163 respondents (68.8%) in the healthy sanitation category. The incidence of stunting in toddlers aged 0-60 months in the Work Area of the Karang Bandar Lampung City Health Center in 2022 was 64 respondents (39.3) and 99 respondents (60.7%) with the category of not stunting. P-Value = 0.006 0.05, it can be concluded that there is a relationship between household environmental sanitation and the incidence of stunting in toddlers aged 0-60 months in the Working Area of the Karang Bandar Lampung Health Center in 2022. Parents are expected to maintain the cleanliness of drinking water sources and sanitation sources, maintain cleanliness and pay attention to clean water sources and latrines with a distance according to health standards. Keywords: Environmental Sanitation, Stunting, Toddlers ABSTRAK Stunting adalah gangguan pertumbuhan linear tubuh anak menjadi pendek atau sangat pendek yang didasarkan pada tinggi badan menurut umur dengan ambang batas (Z-score) -2 SD. Data anak yang mengikuti posyandu di Puskesmas Kota Karang dengan meihat banyaknya anak usia 0 bulan hingga 5 tahun terdapat sejumlah 162 anak, dengan pembagian jumlah berdasarkan usia 5 tahun 36 anak, usia 4 tahun 25 anak, usia 3 tahun 35 anak, usia 2 tahun 40 anak, usia 1 tahun 16 anak, usia 12 bulan 12 anak. Diketahui hubungan sanitasi lingkungan rumah tangga dengan kejadian stunting pada balita usia 0-60 bulan di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2022. Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif, Rancangan dalam penelitian ini menggunakan desain Survei Analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini seluruh anak balita usia 0-60 bulan. Teknik sampling dalam penelitian ini adalah random sampling. Analisa pada uji univariate dan bivariate menggunakan uji chi square. Sanitasi lingkungan rumah tangga di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2023 sebanyak 163 responden (100,0%) dengan kategori sanitasi sehat. Kejadian stunting pada balita usia 0-60 bulan di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2022 sebanyak 64 responden (39,3) dan 99 responden (60,7%) dengan kategori tidak stunting. P-Value = 0,006 0,05 maka dapat disimpulkan terdapat hubungan sanitasi lingkungan rumah tangga dengan kejadian stunting pada balita usia 0-60 bulan di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2022. Bagi orangtua diharapkan menjaga kebersihan sumber air minum dan sumber sanitasi, menjaga kebersihan serta memperhatikan sumber air bersih dan jamban dengan jarak yang sesuai standar kesehatan. Kata Kunci: Sanitasi Lingkungan, Stunting, Balita